Antidepressant Active Ingredients From Chinese Traditional Herb Panax Notoginseng: A Pharmacological Mechanism Review - Li, Yanwei; Guo, Qingwan; Huang, Junqing; Wang, Ziying (Frontiers in Pharmacology, 2022)
Depression is one of the most common mental illnesses in the world and is highly disabling, lethal, and seriously endangers social stability. The side effects of clinical drugs used to treat depression are obvious, and the onset time is longer. Therefore, there is a great demand for antidepressant drugs with better curative effects, fewer side effects, and shorter onset time. Panax notoginseng, a Chinese herbal medication, has been used to treat depression for thousands of years and shown to have a therapeutic effect on depression. This review surveyed PubMed’s most recent 20 years of research on Panax notoginseng’s use for treating depression. We mainly highlight animal model research and outlined the pathways influenced by medicines. We provide a narrative review of recent empirical evidence of the anti-depressive effects of Panax Notoginseng and novel ideas for developing innovative clinical antidepressants with fewer side effects.